The Effect of Workload and Competence on Employee Performance Case Study at the East Perak Health Center, Surabaya City - Nur Idayati (Lavish Opulent Education, 2025)
This study examines the influence of workload and competence on employee performance at the East Perak Health Center in Surabaya, Indonesia. Motivated by fluctuating performance scores and resource limitations in a densely populated service area, this research adopts a quantitative method with a causal design. A sample of 47 healthcare and administrative employees was selected using purposive sampling. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 30. The findings indicate that workload has a significant negative effect on employee performance, while competence shows a significant positive impact. The model explains 51.6% of the variance in employee performance. These results emphasize the critical need to balance workload and enhance employee competence to ensure effective public health service delivery. Future studies are encouraged to explore additional factors affecting performance in community health settings.